Changes in megakaryopoiesis over ontogeny and their implications in health and disease. (17th August 2020) - Davenport, Patricia; Liu, Zhi-Jian; Sola-Visner, Martha
Abstract: A growing body of research has made it increasingly clear that there are substantial biological differences between fetal/neonatal and adult megakaryopoiesis. Over the last decade, studies revealed a developmentally unique uncoupling of proliferation, polyploidization, and cytoplasmic maturation in neonatal MKs that results in the production of large numbers of small, low ploidy, but mature MKs during this period of development, and identified substantial molecular differences between fetal/neonatal and adult MKs. This review will summarize our current knowledge on the developmental differences between fetal/neonatal and adult MKs, and recent advances in our understanding of the underlying molecular mechanisms, including newly described developmentally regulated pathways and miRNAs. We will also discuss the implications of these findings on the ways MKs interact with the environment, the response of neonates to thrombocytopenia, the pathogenesis of Down syndrome-transient myeloproliferative disorder (TMD), and the developmental stage specific-manifestations of congenital amegakaryocytic thrombocytopenia.